The acceptability, knowledge and perceptions of pregnant women toward HIV testing in pregnancy at Ilembe District. - Dube FN; Nkosi ZZ (Curationis, 2008)
This research study aimed to investigate the acceptability, knowledge and perceptions of pregnant women toward HIV testing in pregnancy in Ilembe District. An exploratory research design guided the study. A systematic random sampling was used to select pregnant women who were attending the ante-natal clinic for the first time in their current pregnancy. Self-administered questionnaires with close-ended questions were used in the collection of data. The questions included the women's demographic details, their views of HIV testing, knowledge and as well as their acceptability of HIV testing. Forty questionnaires were distributed and they were all returned. A quantitative method was used to analyse the data. The findings of the study revealed that 45% of the women in the sample were relatively young (18-25 years) and most of them (90%) were unmarried .The majority of women (92.5%) said testing was a good idea and 85% said it was necessary. However only 52.5% said they would opt for HIV testing. The uptake of HIV testing was found to be low. Eighty-seven and a half percent (87.5%) of the women in the sample were of the opinion that HIV testing in pregnancy was of benefit to the mother and her baby. Women in the study were generally found to have a good understanding and good perceptions towards HIV testing in pregnancy, but this was not consistent with their behaviour.